Fitting Scoring Rubrics for Electronic Portfolio to Partial Credit Model According to the Number of Assumed Dimensions (Journal Of Educational and Psychological Researches, 2023)
Abstract The current research aims to reveal the extent to which all scoring rubrics data for the electronic work file conform to the partial estimation model according to the number of assumed dimensions. The study sample consisted of (356) female students. The study concluded that the list with the one-dimensional assumption is more appropriate than the multi-dimensional assumption, The current research recommends preparing unified correction rules for the different methods of performance evaluation in the basic courses. It also suggests the importance of conducting studies aimed at examining the appropriateness of different evaluation methods for models of response theory to the individual according to the number of dimensions.